2013
DOI: 10.1186/ar4207
|View full text |Cite
|
Sign up to set email alerts
|

Implications in the difference of anti-Mi-2 and -p155/140 autoantibody prevalence in two dermatomyositis cohorts from Mexico City and Guadalajara

Abstract: IntroductionAutoantibodies and clinical manifestations in polymyositis/dermatomyositis (PM/DM) are affected by both genetic and environmental factors. The high prevalence of DM and anti-Mi-2 in Central America is thought to be associated with the high UV index of the area. The prevalences of autoantibodies and the clinical manifestations of PM/DM were evaluated comparing two cohorts in Mexico.MethodsNinety-five Mexican patients with PM/DM (66 DM, 29 PM; 67 Mexico City, 28 Guadalajara) were studied. Autoantibod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
51
1
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(68 citation statements)
references
References 28 publications
(52 reference statements)
10
51
1
6
Order By: Relevance
“…Interestingly, a recent study showed that US juvenile patients with DM and relatively high historical UV exposure are at higher risk of having anti-TIF-1γ antibodies. 24 It is known that UV light increases the levels of Mi-2 in keratinocytes (the other antigen targeted more commonly in areas of high UV exposure), 25,26 and it will be important to test if UV light similarly affects TIF-1γ expression, structure, or subcellular localization in the skin.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a recent study showed that US juvenile patients with DM and relatively high historical UV exposure are at higher risk of having anti-TIF-1γ antibodies. 24 It is known that UV light increases the levels of Mi-2 in keratinocytes (the other antigen targeted more commonly in areas of high UV exposure), 25,26 and it will be important to test if UV light similarly affects TIF-1γ expression, structure, or subcellular localization in the skin.…”
Section: Discussionmentioning
confidence: 99%
“…Patients present with classic skin eruptions particularly in sun-exposed areas alongside myositis, and it has been shown that surface ultra-violet (UV) irradiation intensity correlates with phenotype incidence, particularly in women [81,82]. However, a recent study suggests other factors other than UV influence the development of anti-Mi-2 DM, where autoAb frequency was significantly different in two Mexican cohorts, with similar UV exposures [83]. Both adults and children with anti-Mi-2 DM tend to have mild to moderate myositis and have less systemic disease with a low frequency of lung and joint disease [84].…”
Section: Anti-mi-2mentioning
confidence: 93%
“…However, clinical characteristics associated with anti-Mi-2 have not been studied extensively due to limited availability of the immunoassays and relatively low prevalence in PM/DM. One study from Mexico compared clinical features of anti-Mi-2 positive patients vs. others as the prevalence of anti-Mi-2 in this cohort was high (35 % in PM/DM, 45 % in DM) [77]. High CK level before treatment was noted in anti-Mi-2 (+) DM vs. anti-Mi-2 (−) DM (initial CK, >1000 IU/L, 100 vs. 52 %, P <0.0001; initial CK, >5000 IU/L, 54 vs. 14 %, P <0.005).…”
Section: Introductionmentioning
confidence: 99%
“…Although all studies showed the specificity of anti-Mi-2 for DM, reported prevalence of anti-Mi-2 in different studies is quite different even in the same country [77] as summarized in Table 6. Prevalence of anti-Mi-2 in DM varies 5–27 % in Italy and 2–19 % in Japan.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation